Paleomagnetism of mafic dikes from the Avalon Peninsula, eastern Newfoundland - Seguin, M.; Gahé, E.; Khalfi, M. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1982)
As part of a major study of the Avalon zone in eastern Newfoundland, we describe the palromag-netism of two series of dikes located in the Bauline and Colliers-Harbour Main areas, respectively. Detailed alternating field (AF) and thermal experiments performed on these dikes indicate that they are characterized by two significantly different mean directions of magnetization: SE++CD = 153°, I - +62*; K - 46, N = 12 sites) and SW (D - 217°, I - +58°, K - 58, N - 12 sites ) with corresponding paleopole positions at A (A°N, 3A"U; dp,dm - 8", 10°) and C (2"N, 81°W; dp, dm - 6", 9'). Antipoles A and C are located in southerly latitudes, and a comparison with other poles of Avalonian rocks from New Brunswick, Nova Scotia and Newfoundland indicates a Silurian to Siluro-Devonian age for these dikes. Poles A and B are interpreted as representing rapid apparent polar wander with respect to eastern Newfoundland during Silurian time. Two components of magnetization, corresponding to two distinct geological events, are observed in the dikes investigated and this situation favours the following geological scenario for the evolution of the Avalon microcontinent: (a) Intracratonic rift rone resulting in long-lived Late Hadrynian and Cambrian continental extension, (b) a very late phase of distension in separating miniplates during Silurian and Early Devonian time.